Changes in the quality of sweet pepper types during the post-harvest ripening - Orbán Csaba; Füstös Zsuzsanna; Gilinger-Pankotai Maria (Journal on Processing and Energy in Agriculture, 2011)
Our objectives were to find out how the colours of the fruits, the vitamin C content, and the peroxidase enzyme activity changes after harvest in different pepper types. The classification criterion was the colour of surface, which can indicate the level of maturity. The separated fruits were stored for 1 or 2 weeks at 18°C. Our results showed that with half-matured peppers the vitamin C content increased during the first week and after that the values decreased due to dissimilation and ageing processes. With fully-matured peppers, there was a decrease in the vitamin C content from the start of storage. The change of POD activity was similar to the vitamin C content. Within half-matured peppers, it increased in the first period, and then decreased. The fully-matured samples produced stable low values, which changed slightly. Our experiments gave new detailed data about the ripening process of pepper on more maturity levels than previous studies.